Developing teachers' pedagogical identities through a community of practice: learning to sustain the use of a student-centered inquiry as curriculum approach. Issue 8 (13th October 2019) - Luguetti, Carla; Aranda, Raquel; Nuñez Enriquez, Oscar; Oliver, Kimberly L.
ABSTRACT: This collaborative self-study explores how educators' pedagogical identities developed in the process of learning to use a Student-Centered Inquiry as Curriculum (SCIC) approach in activity settings within a community of practice (CoP). Participants included a university professor, college instructor, postdoctoral student and doctoral student. Data included 16 weekly field notes and debriefings following observations, teacher artifacts, 16 weekly collaborative group meetings, and 3 90-minute interviews per teacher. Culture, values, beliefs and professional background were critical for the development of the teachers' pedagogical identities in the process of learning to use a SCIC approach within a community of practice. These experiences created for some, places to further develop their ideas about teaching, whereas for others they caused great discomfort and a sense of personal loss. The CoP facilitated the development of the teachers' pedagogical identities, changing positionalities, and negotiating culture, values, beliefs and professional backgrounds.